Imaging of the Glucose-Dependent Insulinotropic Polypeptide Receptor Using a Novel Radiolabeled Peptide Rationally Designed Based on Endogenous GIP and Synthetic Exendin-4 Sequences - Irina Velikyan; Martin Bossart; Torsten Haack; Iina Laitinen; Sergio Estrada; Lars Johansson; Stefan Pierrou; Michael Wagner; Olof Eriksson (MDPI AG, 2022)
Imaging and radiotherapy targeting the glucose-dependent insulinotropic polypeptide receptor (GIPR) could potentially benefit the management of neuroendocrine neoplasms (NENs), complementing clinically established radiopharmaceuticals. The aim of this study was to evaluate a GIPR-targeting positron emission tomography (PET) radioligand with receptor-specific binding, fast blood clearance, and low liver background uptake. The peptide DOTA-bioconjugate, C803-GIP, was developed based on the sequence of the endogenous GIP(1-30) and synthetic exendin-4 peptides with selective amino acid mutations to combine their specificity for the GIPR and in vivo stability, respectively. The 68Ga-labeled bioconjugate was evaluated in vitro in terms of binding affinity, specificity, and internalization in HEK293 cells transfected with the human GIPR, GLP1, or GCG receptors and in sections of human insulinoma and NENs. In vivo binding specificity, biodistribution, and tissue background were investigated in mice bearing huGIPR-HEK293 xenografts and in a pig. Ex vivo organ distribution, pharmacokinetics, and dosimetry were studied in normal rats. [68Ga]Ga-C803-GIP was stable and demonstrated a high affinity to the huGIPR-HEK293 cells. Binding specificity was demonstrated in vitro in frozen sections of NENs and huGIPR-HEK293 cells. No specific uptake was observed in the negative controls of huGLP1R and huGCGR cells. A novel rationally designed PET radioligand, [68Ga]Ga-C803-GIP, demonstrated promising binding characteristics and specificity towards the GIPR.